Women’s Career Development and Relationships: A Qualitative Inquiry - Lalande, Vivian M.; Crozier, Sharon D.; Davey, Heather (Canadian Journal of Counselling and Psychotherapy, 2007)
Through the use of grounded theory methodology, this study explored how relationships are involved in women's career development. Eighteen female students participated in an unstructured interview. The interviews were transcribed and analyzed using a constant comparative method of analysis. Generally, relationships were found to be important to the women's careers both in terms of how occupations were chosen and the influence people had on their developing self-knowledge and career decisions. Results suggest that relationships may be a central organizing factor in women's career development and that women's career development and psychosocial development are interwoven.